Quality of Biocompost Resulting from Biopore Holes Based on Light Intensity and Acidity Degree (pH) - Arik Pujiyanti; Sulhadi Sulhadi; Mahardika Prasetya Aji (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
The use of chemical fertilizers that are not balanced with the provision of organic fertilizers can damage the soil. Chemical fertilizers can also damage the balance of nutrients in the soil and lower soil pH. Therefore, organic fertilizers are needed to help restore soil fertility and LRB as a medium for composting organic fertilizers. The biopore infiltration hole (LRB) is